2019
DOI: 10.1534/g3.119.400469
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Glycerol on the Utilization of Glucose in Yarrowia lipolytica Using RNA-Seq-Based Transcriptomics

Abstract: Glycerol is considered as a promising substrate for biotechnological applications and the non-conventional yeast Yarrowia lipolytica has been used extensively for the valorization of this compound. Contrary to S. cerevisiae, Y. lipolytica seems to prefer glycerol over glucose and it has been reported previously that the presence of glycerol can suppress the consumption of glucose in co-substrate fermentations. Based on these observations, we hypothesized glycerol repression-like effects in Y. lipolytica, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 47 publications
(57 reference statements)
6
25
3
Order By: Relevance
“…The preference of Y. lipolytica for glycerol is also well documented in literature. The yeast prefers glycerol over glucose and presence of glycerol but not that of glucose represses the uptake of other carbon sources including glucose in co-fermentations [18,19]. Workman et al, (2013) [16] found that glycerol assimilation was accompanied with higher oxygen uptake rates in comparison to glucose and maximum growth rate of Y. lipolytica on glycerol (0.30 h -1 ) was 25% higher than on glucose (0.24 h -1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The preference of Y. lipolytica for glycerol is also well documented in literature. The yeast prefers glycerol over glucose and presence of glycerol but not that of glucose represses the uptake of other carbon sources including glucose in co-fermentations [18,19]. Workman et al, (2013) [16] found that glycerol assimilation was accompanied with higher oxygen uptake rates in comparison to glucose and maximum growth rate of Y. lipolytica on glycerol (0.30 h -1 ) was 25% higher than on glucose (0.24 h -1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis for glycerol preference/repression like effects by Y. lipolytica is that its genome contain only one hexose transporter but three genes linked with glycerol transport [37]. Lubuta et al, (2019) [18] performed RNA-Seq-based transcriptome analysis in Y. lipolytica and argued that the higher expression of several transporters could be potentially related to the phenotypic observation of glycerol preference. A similar kind of phenomenon can be envisaged in the present strain as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, when grown in a medium containing glycerol and glucose, glycerol is consumed first or co-consumed with glucose (Rywińska et al ., 2010), suggesting an as yet unknown regulatory mechanism(s) controlling this behaviour. An attempt to elucidate the background of this phenomenon using whole transcriptome sequencing under carbon limiting conditions has recently been taken (Lubuta et al ., 2019). In the current work, we expand on this by considering the interplay between carbon sources and carbon to nitrogen ratios.…”
Section: Introductionmentioning
confidence: 99%